2007
DOI: 10.1378/chest.132.4_meetingabstracts.567b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bronchoscopic Bronchoalveolar Lavage vs Blind Lavage With a Modified Nasogastric Tube in the Etiologic Diagnosis of Ventilator-Associated Pneumonia

Abstract: Objective. Our objective was to compare the results of a blind lavage vs a bronchoscopic-guided bronchoalveolar lavage for the etiologic diagnosis of ventilator-associated pneumonia (VAP).Design. Prospective study in consecutive patients with high probability of VAP. Every patient underwent both procedures, in a formally randomized fashion. The interpretation of quantitative cultures was done in a blind fashion.Setting. Single center study, with a 20 bed medical and surgical Intensive Care Unit of the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This may be a "likely pandemic scenario" but is less severe than the U.S. Department of Health and Human Services "moderate severity" pandemic scenario (0.3% mortality) (2). It is far less severe than human H5N1 avian flu (50% to 60% mortality), which does not seem to transmit from human to human at this time (9). In the predictions of Nap et al, admission rate and ICU burden flow from their relatively low prediction of mortality.…”
Section: Influenza-associated Encephalopathy and Neurolgic Features Omentioning
confidence: 91%
See 3 more Smart Citations
“…This may be a "likely pandemic scenario" but is less severe than the U.S. Department of Health and Human Services "moderate severity" pandemic scenario (0.3% mortality) (2). It is far less severe than human H5N1 avian flu (50% to 60% mortality), which does not seem to transmit from human to human at this time (9). In the predictions of Nap et al, admission rate and ICU burden flow from their relatively low prediction of mortality.…”
Section: Influenza-associated Encephalopathy and Neurolgic Features Omentioning
confidence: 91%
“…Hypothermia has become critical to organ preservation for transplantation and brain or whole-body preservation during cardiac and neurosurgery. More recently, clinical studies have demonstrated benefit of resuscitative hypothermia post resuscitation from cardiac arrest (8,9) and neonatal hypoxic-ischemic encephalopathy (10).…”
Section: Influenza-associated Encephalopathy and Neurolgic Features Omentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies performed recently have shown that the yield of blind samples is as good as that of bronchoscopic-guided samples. [36][37][38] The possible explanation for their equity is that VAP is diffuse and bilateral in nature; hence, even blind techniques have a high chance of yielding productive samples. Therefore, nonbronchoscopic techniques, being less costly and more readily available, are considered practical alternatives to bronchoscopic BAL/PSB.…”
Section: Bacteriologicalmentioning
confidence: 99%